2004
DOI: 10.1016/j.biolcel.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tissue specific expression of Notch-1 in human tissues

Abstract: Signaling through the Notch cell surface receptors is a highly conserved mechanism of cell fate specification. Notch signaling regulates proliferation, differentiation and cell death. In vertebrates, putative gene duplication has originated four Notch genes, Notch-1, -2, -3 and -4. They have been implicated in neurogenesis, hematopoiesis, T-cell development, vasculogenesis and brain cortical growth. We have investigated Notch-1 distribution in normal human tissues by immunohistochemistry and immunoblot. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Finally, an RMS tissue microarray containing human eRMS, aRMS, and normal skeletal muscle cores was probed for activated Notch1 protein expression, using standard immunohistochemistry, as a surrogate for Hey1 protein expression. As expected in tissues of skeletal muscle origin (19), there was diffuse membrane and cytoplasmic staining of Notch1 in all samples. However, nuclear Notch1 staining, which represents the transcriptionally active form of Notch1, while absent in skeletal muscle and moderately expressed in aRMS, was highly expressed in eRMS (Fig.1C).…”
Section: Resultssupporting
confidence: 84%
“…Finally, an RMS tissue microarray containing human eRMS, aRMS, and normal skeletal muscle cores was probed for activated Notch1 protein expression, using standard immunohistochemistry, as a surrogate for Hey1 protein expression. As expected in tissues of skeletal muscle origin (19), there was diffuse membrane and cytoplasmic staining of Notch1 in all samples. However, nuclear Notch1 staining, which represents the transcriptionally active form of Notch1, while absent in skeletal muscle and moderately expressed in aRMS, was highly expressed in eRMS (Fig.1C).…”
Section: Resultssupporting
confidence: 84%
“…Staining for the NICD, however, was not restricted to fibroblasts and was also prominent in keratinocytes, endothelial cells, pericytes, VSMCs and T cells as described before (figure 1A). 20 Consistent with increased Notch signalling, the mRNA levels of the Notch target gene hes-1 were elevated by 392 Âą 33% in skin biopsy samples of patients with SSc as compared with similar samples from healthy individuals (p < 0.05) (figure 1B). To investigate the mechanisms that activate Notch signalling in SSc, we analysed the expression of Notch ligands and observed an upregulation of Jag-1 mRNA levels by 608 Âą 86% in SSc skin compared with control skin samples (p < 0.05) (figure 1C).…”
Section: Resultsmentioning
confidence: 75%
“…An important exception to this general rule is the epidermal keratinocyte, because we and others have clearly demonstrated that activation of Notch signaling promotes epidermal keratinocyte differentiation (Lowell et al, 2000;Rangarajan et al, 2001b;Nickoloff et al, 2002). Characterizing expression patterns for Notch-1 in human tissues has revealed that in the skin, Notch-1 was expressed by hair follicles, sebaceous glands, and sweat glands (Baldi et al, 2004). In the epidermis, Notch-1 appears to first become apparent in the suprabasal layers corresponding to the cells undergoing initial differentiation (Nickoloff et al, 2002).…”
Section: Notch Signaling As a Proto-oncogene Or Tumor Suppressormentioning
confidence: 95%